Biocompatible and pH-sensitive MnO-loaded carbonaceous nanospheres (MnO@CNSs): A theranostic agent for magnetic resonance imaging-guided photothermal therapy. (September 2018) - Xiang, Ying; Li, Nianlu; Guo, Lijuan; Wang, Hong; Sun, Haofeng; Li, Ruohan; Ma, Long; Qi, Yafei; Zhan, Jinhua; Yu, Dexin
Abstract: Integrated theranostic agents can provide multifunctional platforms for synergetic cancer diagnosis and therapy. However, the efficiency and safety of agents are of great concern. In this work, we prepared biocompatible and pH-sensitive MnO-loaded carbonaceous nanospheres (MnO@CNSs) for simultaneous magnetic resonance imaging (MRI) and photothermal therapy (PTT). Carbonaceous nanospheres (CNSs) with biocompatibility and unique optical properties were prepared by hydrothermal method for photothermal absorption and released Mn 2+ were used for MRI. In vitro the results of MRI T1 relaxivity test showed r1 value in the acidic environment with an increase by 5-fold (from 5.42 mM −1 s −1 to 0.18 mM −1 s −1 ), due to excellent pH responsiveness. In addition, MRI and photothermal effect for mouse model showed enhanced T1 signal and temperature elevation in tumor site with photoirradiation. All the aforementioned results embodied that MnO@CNSs can be used as a fine biocompatible and pH-sensitive contrast for combining targeted MRI with accurate photothermal therapy, showing important value and potential in the integration of theranostics of cancer. Graphical abstract: Image 1